2014
DOI: 10.1111/tbed.12298
|View full text |Cite
|
Sign up to set email alerts
|

Classical Swine Fever in Wild Hog: Report of its Prevalence in Northeast India

Abstract: Classical swine fever virus (CSFV) is the causative agent of a highly contagious disease, hog cholera in pigs. The disease is endemic in many parts of the world and vaccination is the only way to protect the animals from CSFV infection. Wild hogs belong to the species Sus Scrofa Cristatus under the family Suidae are quite susceptible to CSFV infection. The epidemiological role concerning classical swine fever (CSF) in India is largely unknown. We report here the three isolated cases of CSF in wild hogs from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Exceptions are the 2005 outbreak in South Africa and the 2009 outbreak in Israel that were both caused by 2.1 CSFV strains [70,71]. Reports from India are increasingly detailed and demonstrate that sub-genotypes 1.1, 2.1, and 2.2 are co-circulating [72,73,74,75,76,77,78,79]. This changes the historical situation where genotype 1.1 strains predominated.…”
Section: Virus Propertiesmentioning
confidence: 99%
“…Exceptions are the 2005 outbreak in South Africa and the 2009 outbreak in Israel that were both caused by 2.1 CSFV strains [70,71]. Reports from India are increasingly detailed and demonstrate that sub-genotypes 1.1, 2.1, and 2.2 are co-circulating [72,73,74,75,76,77,78,79]. This changes the historical situation where genotype 1.1 strains predominated.…”
Section: Virus Propertiesmentioning
confidence: 99%
“…Regarding molecular phylogenetic studies of pestiviruses in the north eastern part of India, several reports have been published stating prevalence of CSFV subgenotype 1.1 and emergence of subgenotype 2.2 in the region [ 47 ]. Recently, CSFV of genotype 2.2 from wild hog has also been reported from the region [ 48 ]. Overall results in our laboratory showed that the CSFV isolates from India, Nepal and China might have some common ancestor and subgenotype 2.2 is wide spread in the north- eastern region of India.…”
Section: Discussionmentioning
confidence: 99%
“…Some countries, such as Australia, North America, and New Zealand have successfully eradicated the disease through the fulfillment of regulatory measures 3 . However, the disease is still existent in other parts of the world, for instance, Madagascar, Singapore, Laos, Lithua-nia, Myanmar, Colombia, and Republic of Korea, impeding the development of animal husbandry 4 6 .…”
Section: Introductionmentioning
confidence: 99%